Exploring neuropsychiatric manifestations of vitamin B complex deficiencies - Han, Anamaria; Almeida, Leandro; Anand, Nikhilesh; Salloum, Ihsan M.; Kanaan, Salim; Gadad, Bharathi S.; Daher, João Paulo Lima (Frontiers in Psychiatry, 2025)
B complex vitamins, a group of eight water-soluble vitamins, play interconnected roles in maintaining nervous system health. Thiamine (B1), riboflavin (B2), and niacin (B3) are essential as co-enzymes in numerous metabolic reactions related to energy production. Thiamine is involved in the Krebs cycle, riboflavin in the electron transport chain, and niacin plays a key role in both glycolysis and the Krebs cycle. These metabolic processes are vital for sustaining the integrity of the nervous system, as the energy produced is critical for the functioning of nerve cells. Deficiencies in these vitamins can lead to significant neurological and psychiatric conditions, including Wernicke Korsakoff syndrome, Parkinson’s disease, and various mental illnesses. Additionally, pyridoxine (B6), folate (B9), and cobalamin (B12) are indispensable coenzymes for the methylation of homocysteine to methionine, a process critical to nervous system function. Elevated homocysteine levels, resulting from deficiencies of these vitamins, are associated with higher risks of depression and dementia. Thus, imbalances in these vitamins can disrupt key biochemical pathways, leading to neuropsychiatric disorders. The literature reviewed underscores the importance of daily intake of B complex vitamins to maintain normal serum levels and optimal neuronal function. This review aims to elucidate the neuropsychiatric manifestations associated with deficiencies in these vitamins.